Anodic characteristics and electrochemical machining of two typical γ-TiAl alloys and its quantitative dissolution model in NaNO3 solution. (20th January 2020) - Wang, Yudi; Xu, Zhengyang; Zhang, An
Abstract: Electrochemical machining (ECM) is a promising machining method for lightweight γ-TiAl alloys, owing to several advantages over traditional methods. In this work, the electrochemical and ECM experiments of two typical γ-TiAl alloys (Ti–48Al–2Cr–2Nb and Ti–45Al–2Mn–2Nb+0.8 vol% TiB2 XD) in NaNO3 solution are carried out to obtain their anodic dissolution characteristics, and some special phenomena are analyzed in detail. The polarisation behaviour of anode is measured by polarisation curve and cyclic voltammetry. The composition and structure of the passive film on the surface of anode are determined by X-ray photoelectron spectroscopy and electrochemical impedance spectroscopy. The results show that the passive film is mainly composed of TiO2 and Al2 O3, and its structure consists of a loose outer film and a dense inner film. ECM flat experiments at different feed rates are also carried out, where it is found that the lamellar microstructure of the two alloys is fully exposed. For TiAl 4822, there are lamellar and non-lamellar regions on the surface of the workpieces, and the direction of the lamella in the different lamellar colonies is also different. For TiAl 45XD, however, some protruding needle-like and globular TiB2 exist on the processed surface, which is the main factor influencing the surface quality. Finally, a quantitative dissolution model is also proposed to characterise the dissolution behaviour of TiAl 4822 and TiAl 45XD in 20%NaNO3 solution. Highlights: The polarisation behaviour of the specimens is measured by polarisation and CV curves. The composition of passive film are mainly composed of TiO2 and Al2 O3 . An EEC model of passivation film with inner dense layer and outer porous layer is proposed. A schematic model is proposed to characterise the passive film structure. The dissolution mechanism of TiAl 4822 and TiAl 45XD is revealed.